Nivel de conocimiento de apoderados sobre el contenido de lonchera escolar y evaluación nutricional de los estudiantes de la I.E 2199 El Porvenir, 2018 - Infantes Ruiz, Lesly Leonila (2019)
The Level of knowledge of parents about the content of school lunch box and nutritional evaluation of the students of I.E 2199 El Porvenir, 2018 was determined. The sample consisted of 50 parents and 50 children. To determine the knowledge that the attorneys have about the school lunch box, a survey was used and for the nutritional status of the children the anthropometric measures were used. It was found that the level of knowledge of the parents over the school lunch box was of medium level with 52% , followed by 30% of low level and 18% with high level, with respect to the nutritional evaluation, according to the BMI of the children it was obtained that 64% of the students evaluated have alteration of nutritional status where 4% have low weight , 16% were overweight, 4% had obesity, 12% obesity grade 1, 14% had obesity grade 2 and 14% had obesity grade 3, only 36% had a normal weight. According to the Chi-Cuadrado, it was determined that the parents have a medium level of knowledge about the content of a school lunch box and the students have a nutritional status with a normal BMI of p <0.05. It was concluded that the level of knowledge of a school lunch box of the parents is significantly related to the nutritional status of the students of the I.E 2199 El Porvenir, 2018